KECEMASAN MEMBACA BAHASA JEPANG PADA MAHASISWA ANGKATAN 2021 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Azizah Safira; Merri Silvia Basri; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Foreign language reading anxiety has a negative effect on cognitive processes and behavior because in language classes between physical, cognitive, and behavioral anxiety are symptoms that influence each other. A quantitative descriptive methodology was used in this research. The purpose of this research was to determine the level of reading anxiety students class of 2021 Japanese Language Education Study Program FKIP Riau University. Respondents in this reseacrh were 30 students of 2021 Japanese Language Education Study Program in Riau University. Researchers used data collection techniques in the form of questionnaires using FLRAS instruments (Ahmad, 2013). The results showed that as many as 4 students or 13% had low reading anxiety levels, 21 students or 70% had a medium level of anxiety, and 5 students or 17% had a high level of anxiety.Key Words : japanese language anxiety, reading anxiety, anxiety level, FLRAS